Computational Study on Sensing Properties of Pd‐Decorated Phosphorene for Detecting Acetone, Ethanol, Methanol, and Toluene—A Density Functional Theory Investigation. Issue 11 (4th October 2021) - Aasi, Aref; Aghaei, Sadegh Mehdi; Bajgani, Sahar Ebrahimi; Panchapakesan, Balaji
Abstract: Late reports on the application of black phosphorene for gas sensing have raised great attention to this remarkable 2D material. In this regard, the sensing behavior of phosphorene toward a group of volatile organic compounds (VOCs) is scrutinized. The studied gas molecules are acetone, ethanol, methanol, and toluene as main members of VOCs, along with CO2 and H2 O gas molecules. The adsorption of the gases on the pristine and Pd‐decorated phosphorene is studied by employing first‐principles density functional theory (DFT) combined with non‐equilibrium Green's function (NEGF). It is divulged that the selected molecules are weakly adsorbed upon the pristine phosphorene, but after decoration with Pd atom, the adsorption energy, and net charge transfer are improved. It is discovered based on the moderate adsorption energy and large charge transfer for acetone on the Pd‐decorated phosphorene that it can be a suitable sensor for acetone detection. Additionally, recovery time of 2.57 s at the temperature of 350 K, and under ultraviolet (UV) light is achieved after decoration for detection of acetone. Therefore, the authors' theoretical investigations help to better understand the adsorption mechanism of Pd‐decorated phosphorene as a gas sensor and provide a facile approach to broaden its application in industrial, medical, and environmental monitoring. Abstract : Pd‐decorated phosphorene is a potential reusable gas sensor at room temperature for volatile organic compounds (VOC) gas molecules especially toward acetone detection with a recovery time of 2.57 sand adsorption energy of 1.14 eV. The obtained results after decoration with Pd atom encourage further experimental inspections in the development of such a nano‐sensor platform.